2009
DOI: 10.1016/j.jvc.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The T wave in the V10 precordial electrocardiographic lead is negative in healthy Chihuahua dogs

Abstract: Objectives: The T wave polarity in the V10 precordial electrocardiographic (ECG) lead in Chihuahuas is described as positive in the veterinary literature. The aim of this study was to investigate the polarity of the T wave in the V10 precordial ECG lead in clinically healthy Chihuahuas. Our null hypothesis was that healthy Chihuahuas have a negative T wave in V10. Animals, materials and methods: In this prospective study, 67 healthy breederowned Chihuahuas were used. A physical examination, 10-lead ECG and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This possible exception or "peculiarity" of Chihuahuas have been replicated in many subsequent publications (Ettinger & Sutter, 1970;Bolton, 1975;Tilley et al, 1985;Miller & Tilley,1988;Ware, 1994;Smith Jr. & Hadlock, 1995;1;Smith Jr. & Fox, 1999;Nelson 2000;Montoya & Ramirez, 2007;Cotté & Ettinger, 2008;Filippi 2011;Macintire et al, 2012;Mazzini & Prada, 2020;Pascon 2021;Schroeder, 2021). Contradicting this discrepancy, Dijkstra and Szatmári (2009) reported that in Chihuahuas the T-wave in lead V10 is usually negative, rather than positive; therefore, it would not constitute an exception among the different canine breeds. This research study aimed to clarify the polarity and shape of the T-wave in the lead V-10 in a group of healthy Chihuahuas.…”
Section: Introductionmentioning
confidence: 99%
“…This possible exception or "peculiarity" of Chihuahuas have been replicated in many subsequent publications (Ettinger & Sutter, 1970;Bolton, 1975;Tilley et al, 1985;Miller & Tilley,1988;Ware, 1994;Smith Jr. & Hadlock, 1995;1;Smith Jr. & Fox, 1999;Nelson 2000;Montoya & Ramirez, 2007;Cotté & Ettinger, 2008;Filippi 2011;Macintire et al, 2012;Mazzini & Prada, 2020;Pascon 2021;Schroeder, 2021). Contradicting this discrepancy, Dijkstra and Szatmári (2009) reported that in Chihuahuas the T-wave in lead V10 is usually negative, rather than positive; therefore, it would not constitute an exception among the different canine breeds. This research study aimed to clarify the polarity and shape of the T-wave in the lead V-10 in a group of healthy Chihuahuas.…”
Section: Introductionmentioning
confidence: 99%